Assessing the non-inferiority of prosthesis constructs used in total and unicondylar knee replacements using data from the National Joint Registry of England, Wales, Northern Ireland and the Isle of Man: a benchmarking study. Issue 4 (29th April 2019) - Deere, Kevin C; Whitehouse, Michael R; Porter, Martyn; Blom, Ashley W; Sayers, Adrian
Abstract : Objectives: To investigate the relative performance of knee replacement constructs compared with the best performing construct and illustrate the substantial variability in performance. Design: A non-inferiority study. Setting: England and Wales. Participants: All primary total and unicondylar knee replacements performed and registered in the National Joint Registry between 1 April 2003 and 31 December 2016. Main outcome measures: Kaplan-Meier failure function for knee replacement constructs. Failure difference between best performing construct (the benchmark) and other constructs. Methods: Using a non-inferiority analysis, the performance of knee replacement constructs by brand were compared with the best performing construct. Construct failure was estimated using the 1-Kaplan Meier method, that is, an estimate of net failure. The difference in failure between the contemporary benchmark construct and all other constructs were tested. Results: Of the 449 different knee replacement constructs used, only 27 had ≥500 procedures at risk at 10 years postprimary, 18 of which were classified as inferior to the benchmark by at least 20% relative risk of failure. Two of these 18 were unicondylar constructs that were inferior by at least 100% relative risk. In men, aged 55–75 years, 12 of 27 (44%) constructs were inferior by at least 20% to the benchmark at 7 years postprimary. In women, aged 55–75 years, 8 of 32 (25%) constructs were inferior at 7 years postprimary. Very few constructs were classified as non-inferior to the contemporary benchmark. Conclusions: There are few knee replacement constructs that can be shown to be non-inferior to a contemporary benchmark. Unicondylar knee constructs have, almost universally, at least 100% worse revision outcomes compared with the best performing total knee replacement. These results will help to inform patients, clinicians and commissioners when considering knee replacement surgery.